SISTEM PENDUKUNG KEPUTUSAN DALAM MENENTUKAN PRIORITAS PENDISTRIBUSIAN DARAH MENERAPKAN METODE THE EXTENDED PROMETHEE II PADA KANTOR PALANG MERAH INDONESIA(PMI) - Rahma Dewi (STMIK Budi Darma, 2019)
PMI (Indonesian Red Cross) is a national association organization in Indonesia engaged in the field of social humanity. In carrying out its duties PMI does not make a difference but rather prioritizes victims who most need immediate help for the safety of their souls. The Indonesian Red Cross Office (PMI) Medan provides a reward or award with the aim of improving the performance of the blood distribution process in charge, and to determine the priority of blood distribution, alternatives and criteria are needed to become a reference in the selection process. Decision Support System is one way that can be used in the priority process of blood distribution. In this study, the authors used the Extended Promethee II (Exprome II) method to find the weight value of the criteria, and to find the final value or to find the priority value of blood distribution. Thus a Decision Support System is needed in order to help the Indonesian Red Cross (PMI) Medan to determine the priority of blood distribution.Keywords: Decision Support System, The Extended Promthee II, Priority Selection of Blood distribution